Advanced glycation endproducts: from precursors to RAGE: round and round we go - Ramasamy, Ravichandran (2010)
The formation of advanced glycation end-products (AGEs) occurs in diverse settings such as diabetes, aging, renal failure, inflammation and hypoxia. The chief cellular receptor for AGEs, RAGE, transduces the effects of AGEs via signal transduction, at least in part via processes requiring the RAGE cytoplasmic domain binding partner, diaphanous-1 or mDia1. Data suggest that RAGE perpetuates the inflammatory signals initiated by AGEs via multiple mechanisms. AGE–RAGE interaction stimulates generation of reactive oxygen species and inflammation—mechanisms which enhance AGE formation. Further, recent data in type 1 diabetic kidney reveal that deletion of RAGE prevents methylglyoxal accumulation, at least in part via RAGE-dependent regulation of glyoxalase-1, a major enzyme involved in methylglyoxal detoxification. Taken together, these considerations place RAGE in the center of biochemical and molecular stresses that characterize the complications of diabetes and chronic disease. Stopping RAGE-dependent signaling may hold the key to interrupting cycles of cellular perturbation and tissue damage in these disorders.